A gap analysis of teaching marketing ethics: Desired versus current state. Issue 7 (3rd October 2019) - Paul, Pallab
Abstract: There is a consensus among marketing educators, scholars, and practitioners that business ethics, in particular, and marketing ethics must be a vital part of a marketing student's education. However, a survey of the best business schools in the United States reveals that most of them do not offer a stand-alone business ethics course, let alone a marketing ethics course. The author provides a gap analysis of the desired versus current state of marketing ethics education. Recommendations on how to bridge these gaps are provided.